CyTOF: An Emerging Technology for Single‐Cell Proteomics in the Mouse. Issue 4 (22nd April 2021) - Tracey, Lauren J.; An, Yeji; Justice, Monica J.
Abstract: The ability to analyze the proteome of single cells is critical for the advancement of studies of steady‐state and pathological processes. Mass cytometry, or CyTOF, combines principles of mass spectrometry and flow cytometry to enable single‐cell analysis of protein expression. CyTOF can simultaneously assess DNA content and proteins and has the capacity to measure 40 to 100 parameters in each cell. Applying this technology to tissues or cells on slides, termed imaging mass cytometry (IMC), allows for visualization of normal and diseased tissues in situ. The high‐dimensional proteomic analysis that can be undertaken with CyTOF and IMC has the potential to enhance our understanding of complex and heterogeneous developmental and disease pathways. This article will describe the CyTOF experimental workflow, including reagent selection, sample preparation, and data analysis. CyTOF is compared to flow cytometry, focusing on the strengths and weaknesses of these powerful techniques. Importantly, we review key studies in mouse models of human disease that highlight the strength of CyTOF and IMC to drive discovery research and therapeutic advancement. © 2021 Wiley Periodicals LLC.